THE PECULIARITIES OF INTERNET-BASED MATERIALS IN TEACHING WRITING (Journal of Universal Science Research, 2023)
The rapid development of the Internet in the 1990s has had a widespread impact on students' learning and knowledge acquisition in terms of foreign language learning. From this moment on, the Internet becomes an extraordinary source of information in the practice of teaching foreign languages. This article attempts to highlight the main advantages of using the Internet and modern computer technologies in the practice of teaching foreign languages.